2018
DOI: 10.3389/fmicb.2018.01014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis and Clonal Population Structure of Antibiotic Resistance in Campylobacter jejuni Isolated From Broiler Carcasses in Belgium

Abstract: Human campylobacteriosis is the leading food-borne zoonosis in industrialized countries. This study characterized the clonal population structure, antimicrobial resistance profiles and occurrence of antimicrobial resistance determinants of a set of Campylobacter jejuni strains isolated from broiler carcasses in Belgium. Minimum inhibitory concentrations (MICs) against five commonly-used antibiotics (ciprofloxacin, nalidixic acid, tetracycline, gentamicin, and erythromycin) were determined for 204 C. jejuni iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 47 publications
8
29
0
1
Order By: Relevance
“…Phenotypic screening of antimicrobial resistance frequencies among the clinical C. jejuni isolates tested in this study revealed high resistance rates to nalidixic acid (55.8%), ciprofloxacin (56.3%), and tetracycline (49.7%). In Belgium, similarly high resistance rates to these antimicrobials in broiler carcasses were reported in different recent epidemiological studies [35,52]. Therefore, the continued overuse of antibiotics in the case of poultry, which is the main reservoir of Campylobacter spp., is proposed to be responsible, at least in part, to the alarming elevated rate of AMR in Belgium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Phenotypic screening of antimicrobial resistance frequencies among the clinical C. jejuni isolates tested in this study revealed high resistance rates to nalidixic acid (55.8%), ciprofloxacin (56.3%), and tetracycline (49.7%). In Belgium, similarly high resistance rates to these antimicrobials in broiler carcasses were reported in different recent epidemiological studies [35,52]. Therefore, the continued overuse of antibiotics in the case of poultry, which is the main reservoir of Campylobacter spp., is proposed to be responsible, at least in part, to the alarming elevated rate of AMR in Belgium.…”
Section: Discussionmentioning
confidence: 82%
“…Multi-locus sequence typing (MLST) is widely applied for studying the epidemiology of campylobacteriosis. MLST can also be used to track the dissemination of antimicrobial-resistant C. jejuni strains [34,35]. Different recent studies supported the clonal expansion of antimicrobial-resistant C. jejuni strains by revealing an association between different sequence types (STs) and antimicrobial resistance [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The only difference reaching statistical significance was an increase in prevalence of an A103V mutation in rplV (encoding L22), rising from 7.6% in IID1 to 19.6% in ENIGMA (p = 0.034). A103V mutations in L22 have been reported previously in erythromycin-resistant Campylobacter isolates, though the mutation can also occur in susceptible isolates [38,39]. Mutations in the 23S rRNA gene (position 2074 or 2075) have also been implicated in resistance to erythromycin [38].…”
Section: Mutations In Genes Associated With Macrolide Resistancementioning
confidence: 92%
“…Campylobacter can colonize poultry, swine, and ruminants (Gallay et al, 2007;Elhadidy et al, 2018); therefore, people are easily infected when handling and consuming raw and semiraw contaminated foods, as well as contaminated water (Klein-Jöbstl et al, 2016;Kovanen et al, 2016). Most Campylobacter infections are mild, self-limiting, and resolve within a few days.…”
Section: Introductionmentioning
confidence: 99%